Factors Moderating the Influence of Business Networks on Entrepreneurship Development: A Systematic Narrative Review - Severina M. KHAMIDOVA; Yanqing WANG (Communications of International Proceedings, 2022)
Given the state of existent research on how business networks contribute to entrepreneurship, a systematic narrative review is both timely and appropriate. Therefore, a systematic narrative review of the articles published between 1995 and 2020 was conducted in several steps. First, a search of three databases was undertaken using the keywords “business network*” AND entrepreneur*. Second, the results of the search were reviewed using a narrative synthesis methodology with descriptive and thematic analyses, and data synthesis. This review required that articles meet a set of exclusion criteria. These articles investigated the factors of business networks that affect entrepreneurship development. A systematic narrative review of the 35 articles revealed that two moderating factors play key roles in the degree of effectiveness that business networks have in influencing entrepreneurship development (network management and network environment). In addition, both factors are shaped by demographic and firm characteristics. Such information should inform entrepreneurs when assessing how to ensure higher performance and survival of their firms.
Keywords: business networks; entrepreneurship; review